Parents' perception of health-related quality of life in children and adolescents with excess weight - Melissa Maria Romero Nascimento; Tatiana Rocha Melo; Rogério Melo Costa Pinto; Nívea Macedo Oliveira Morales; Tânia Maria Silva Mendonça; Helena Borges Martins da Silva Paro; Carlos Henrique Martins Silva (Elsevier, 2016)
Objective: To evaluate the perception of parents or caregivers on the health-related quality of life (HRQOL) of children/adolescents with overweight/obesity and possible factors associated with this perception. Methods: This was a cross-sectional study involving 297 caregivers of children and adolescents with normal weight (n = 170) and with overweight/obesity (n = 127), from public and private schools in the study municipality. HRQOL scores obtained through the Child Health Questionnaire - Parent Form 50 (CHQ-PF50) were compared according to the nutritional status and gender of the children/adolescents. Multiple regression analysis was used to determine the predictive value of studied variables for the variation in HRQOL scores. Results: Parents of children/adolescents with overweight/obesity attributed lower HRQOL scores to their children in the following domains: physical functioning (p < 0.01; d = 0.49), self-esteem (p < 0.01; d = 0.38), parental impact-emotional (p < 0.05; d = 0.29), family cohesion (p < 0.05; d = 0.26), physical summary score (p < 0.05; d = 0.29), and psychosocial summary score (p < 0.05; d = 0.25). In the multiple regression models, the variables with the highest contribution to the variation in HRQOL scores were: in the physical functioning domain, parental impact-time (β = 0.23; p < 0.05); self-esteem, nutritional status (β = −0.18; p ≤ 0.01); emotional impact on parents, impact on parents' time (β = 0.31; p < 0.05); and in family cohesion, global behavior (β = 0.30; p < 0.05). Conclusions: A negative impact on HRQOL of children/adolescents with overweight/obesity was observed in the physical and psychosocial aspects. The nutritional status was the variable with the greatest contribution for the assessment the self-esteem of children and adolescents in this study. Resumo: Objetivo: Avaliar a percepção dos pais ou cuidadores a respeito da qualidade de vida relacionada à saúde (QVRS) de crianças/adolescentes com sobrepeso/obesidade e os possíveis fatores associados a essa percepção. Métodos: Estudo transversal com a participação de 297 cuidadores de crianças e adolescentes eutróficos (n = 170) e com sobrepeso/obesidade (n = 127), provenientes de escolas públicas e privadas do município do estudo. Escores de QVRS obtidos por meio do Child Health Questionnaire - Parent Form 50 (CHQ-PF50) foram comparados de acordo com o estado nutricional e sexo das crianças/adolescentes. Análises de regressão múltipla foram utilizadas para determinar o valor preditivo das variáveis estudadas para a variação dos escores de QVRS. Resultados: Pais de crianças/adolescentes com sobrepeso/obesidade atribuíram menores escores de QVRS para seus filhos nos domínios: função física (p < 0,01; d = 0,49), autoestima (p < 0,01; d = 0,38), impacto emocional dos pais (p < 0,05; d = 0,29), coesão familiar (p < 0,05; d = 0,26), Sumário do escore físico (p < 0,05; d = 0,29) e Sumário do escore psicossocial (p < 0,05; d = 0,25). Nos modelos de regressão múltipla, as variáveis com maior contribuição para a variação dos escores de QVRS foram: no domínio função física, impacto no tempo dos pais (ß = 0,23; p < 0,05); autoestima, estado nutricional (ß = -0,18; p ≤ 0,01); impacto emocional nos pais, impacto no tempo dos pais (ß = 0,31; p < 0,05); coesão familiar, comportamento global (ß = 0,30; p < 0,05). Conclusões: Há impacto negativo na QVRS de crianças/adolescentes com sobrepeso/obesidade em aspectos físicos e psicossociais. O estado nutricional foi a variável de maior contribuição para a avaliação da autoestima das crianças e adolescentes do presente estudo. Keywords: Quality of life, Child, Adolescents, Overweight, Obesity, Self-image, Palavras-chave: Qualidade de vida, Criança, Adolescente, Sobrepeso, Obesidade, Autoimagem